2016
DOI: 10.5935/1518-0557.20160045
|View full text |Cite
|
Sign up to set email alerts
|

Fertility-preservation in endometrial cancer: is it safe? Review of the literature

Abstract: Almost 5% of women with endometrial cancer are under age 40, and they often have well-differentiated endometrioid estrogen-dependent tumors. Cancer survival rates have improved over the last decades so strategies to avoid or reduce the reproductive damage caused by oncologic treatment are needed. We reviewed the published literature to find evidence to answer the following questions: How should we manage women in reproductive age with endometrial cancer? How safe is fertility preservation in endometrial cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 78 publications
0
30
0
2
Order By: Relevance
“…Some patients cannot be operated on due to advanced age, morbid obesity, and/or medical comorbidities [2,17]. In addition, some young patients wish to preserve their fertility [2,28]. Thus, surgical staging cannot be performed and intra-abdominal or extrauterine spread of the disease cannot be seen in these cases.…”
Section: Roc Curvementioning
confidence: 99%
“…Some patients cannot be operated on due to advanced age, morbid obesity, and/or medical comorbidities [2,17]. In addition, some young patients wish to preserve their fertility [2,28]. Thus, surgical staging cannot be performed and intra-abdominal or extrauterine spread of the disease cannot be seen in these cases.…”
Section: Roc Curvementioning
confidence: 99%
“…There are many reports of ovarian function deterioration after radiation or chemotherapy in premenopausal women [20][21][22][23]. These cases demonstrate that preserving the ovaries does not result in Endometrial cancer in premenopausal women has been shown to be hormone related, have early stage, no myometrial invasion, and good prognosis [24]. If metastatic or synchronous malignancy has not been found in the ovary during surgery, ovarian preservation may be performed; therefore, surgical menopause of the patient is not induced, which may be more beneficial to women's health.…”
Section: Resultsmentioning
confidence: 99%
“…13 Em diversos estudos de tratamento com progestativos a eficácia atinge valores de cerca de 90%. 14 As doentes devem ser criteriosamente selecionadas com base no grau de diferenciação do tumor G1 e tipo histoló-gico endometrioide, no estádio avaliado em RM sem invasão do miométrio e na ausência de invasão linfovascular, e devem ser devidamente informadas de que o tratamento adequado nestas situações é a histerectomia total com anexectomia bilateral, devendo estar dispostas a aceitar os riscos inerentes ao tratamento conservador.…”
Section: Discussionunclassified
“…A eficácia destes regimes varia de 26% a 89% nos casos de tumores que expressam recetores de estrogénio e progesterona. [8][9][10][11][12][13][14] Como alternativa, alguns estudos reportam que a utilização do dispositivo intrauterino com levonorgestrel (SIU) pode obter respostas entre 40% a 100% nas mulheres pré-menopáusicas com estádios precoces de CE bem diferenciado, [9][10][11][12] havendo uma meta-análise que demonstrou menores efeitos secundários do SIU (menor aumento de peso, menos alterações do sono, do humor e da libido, menos enxaquecas), quando comparado com os progestativos orais. 11 As recidivas são frequentes e podem atingir os 50%.…”
Section: Introductionunclassified